Novel approaches to diagnosis and prevention of bovine fatty liver - Morey, Scott D. (Kansas State University, 2010)
The prevalence of fatty liver in transition dairy cattle has been reported to be as high as 50%. There are a few reliable on-farm diagnostic tools and even fewer methods to effectively prevent fatty liver. Non-alcoholic steatohepatitis, an advanced form of non-alcoholic fatty liver in humans, is accurately diagnosed with a commercial blood test that detects plasma cytokeratin-18 (CK18) fragments released during hepatocyte apoptosis. A study was performed using 89 Holstein cows in early lactation to determine if CK18 could serve as a novel indicator of liver triglyceride (TG) content. Although no previous work has been done with CK18 in bovine plasma, our results indicated that CK18 fragments were present in plasma. However, CK18 concentrations did not correlate with liver TG content or other measures of liver function, suggesting it is not a reliable diagnostic tool. Nevertheless, based on liver TG, plasma non-esterified fatty acid (NEFA), and plasma β-hydroxybutyric acid (BHBA) concentrations, this sample population as a whole was not suffering from severe metabolic problems or fatty liver, making it possible that plasma CK18 fragments are elevated only in the most extreme cases. Currently, there is no widely-adopted preventative strategy for fatty liver. A second study was performed to evaluate if encapsulated niacin (EN) could prevent liver TG accumulation during the transition period. Twenty-four primiparous (n=9) and multiparous (n=13) cows were randomly assigned to receive 0 or 24 g of dietary EN, beginning 3 weeks prior to expected calving until 21 days postpartum. Feeding EN did not influence liver TG content, but decreased plasma NEFA concentrations, suggesting inhibition of lipolysis. Multiparous EN cows also experienced depressed dry matter intake (DMI) in the 4 days prior to calving. However, even when EN reduced DMI, plasma NEFA was still suppressed. A novel finding was the prolonged clearance of caffeine in plasma on day 7 postpartum in EN-treated animals. In contrast to other studies, this dose and delivery method of EN did not result in an increase in plasma NEFA after EN treatment ended. These research projects determined that plasma CK18 is likely not a useful diagnostic tool for mild to moderate bovine fatty liver and that feeding EN can inhibit lipolysis but may influence DMI as well. This is one of the first studies into the metabolic effects of feeding EN, and further research is needed in this field.
Keywords: Fatty liver; Niacin; Cytokeratin-18; Dairy cattle; Transition; Agriculture, Animal Pathology (0476); Biology, Animal Physiology (0433); Biology, Veterinary Science (0778)